2018
DOI: 10.1080/15548627.2017.1389823
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy and inflammation in chronic respiratory disease

Abstract: Persistent inflammation within the respiratory tract underlies the pathogenesis of numerous chronic pulmonary diseases including chronic obstructive pulmonary disease, asthma and pulmonary fibrosis. Chronic inflammation in the lung may arise from a combination of genetic susceptibility and environmental influences, including exposure to microbes, particles from the atmosphere, irritants, pollutants, allergens, and toxic molecules. To this end, an immediate, strong, and highly regulated inflammatory defense mec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
297
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 392 publications
(309 citation statements)
references
References 113 publications
(175 reference statements)
11
297
0
1
Order By: Relevance
“…Studies have confirmed that the inhibition of adipose-specific autophagy leads to the increased number of adipocytes with features of brown adipocytes. This facilitated fatty acid oxidation and increased insulin sensitivity both in vitro and in vivo [26]. We speculate that Mark4, autophagy, and browning of white adipose tissue have certain linkages, whether Mark4 can influence autophagy has not been reported.…”
Section: Discussionmentioning
confidence: 87%
“…Studies have confirmed that the inhibition of adipose-specific autophagy leads to the increased number of adipocytes with features of brown adipocytes. This facilitated fatty acid oxidation and increased insulin sensitivity both in vitro and in vivo [26]. We speculate that Mark4, autophagy, and browning of white adipose tissue have certain linkages, whether Mark4 can influence autophagy has not been reported.…”
Section: Discussionmentioning
confidence: 87%
“…Evidence suggests emphysema is caused by accelerated ageing of lung tissues and is associated with flawed endogenous antiageing (sirtuins) and autophagy mechanisms [106][107][108]. This process leads to eventual telomere shortening, cellular senescence, and the development of COPD [109,110]. Oxidative stress is another key driver of COPD pathogenesis.…”
Section: Molecular Mechanisms Of Disease Progressionmentioning
confidence: 99%
“…Autophagy is a well-organized homeostatic cellular process through which diverse cytoplasmic cargos are captured and destroyed to replenish energy sources and amino acids during metabolic stress. 1,2 Autophagy process comprises three steps: the first step is when autophagy-related gene (ATG) drives the cupshaped isolation membrane to decompose into phagophores with omegasome, an autophagic intermediate formed by the endoplasmic reticulum, in the cytosol. Next, the phagophores sequester the cell contents used for autophagy and form autophagosome with a double-membrane structure by elongation and closure.…”
mentioning
confidence: 99%